1968
DOI: 10.1161/01.cir.38.5.846
|View full text |Cite
|
Sign up to set email alerts
|

Muscular Subaortic Stenosis

Abstract: Eleven patients with muscular subaortic stenosis were studied by use of combined right and transatrial septal left heart catheterization. A variety of stimulating maneuvers were performed to induce or increase the functional outflow tract obstruction; 150 pug/kg of propranolol was administered intravenously, and the stimulating maneuvers were repeated. Outflow obstruction was latent (present only with stimulation) in four patients, labile (present intermittently at rest) in five patients, and persistent and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…They are effective in the relief of ischemic chest discomfort and may attenuate exercise-induced LVOT obstruction and resulting dyspnea as well 230 . Disopyramide, a negative inotropic agent, when added to a beta blocker may reduce symptoms further in patients with LVOT obstruction 231 .…”
Section: Managementmentioning
confidence: 99%
“…They are effective in the relief of ischemic chest discomfort and may attenuate exercise-induced LVOT obstruction and resulting dyspnea as well 230 . Disopyramide, a negative inotropic agent, when added to a beta blocker may reduce symptoms further in patients with LVOT obstruction 231 .…”
Section: Managementmentioning
confidence: 99%
“…Furthermore, b-blockers are used in HCM to control the arrhythmic burden in patients with frequent supraventricular or ventricular ectopies, and for rate control in patients with atrial fibrillation. Propranolol was the first b-blocker used and in old studies showed a significant benefit for symptoms associated with a significant reduction in LVOTO [23][24][25][26][27]. More selective beta blockers such as nadolol and bisoprolol are equally effective in controlling exercise induced LVOTO [28].…”
Section: Medical Therapymentioning
confidence: 99%
“…Gene specific treatment has yet to enter clinical practice but is likely to play a role in the future. β blockers are recommended as first line therapy in HCM with symptomatic left ventricular outflow tract obstruction 35565758. ESC guidelines recommend titration to maximum dose and use of disopyramide or invasive and surgical options if symptom control remains problematic 35…”
Section: How Are the Inherited Cardiomyopathies Managed?mentioning
confidence: 99%